Radiation attenuation characterization of some biological samples by using the Klein-Nishina formula - Levet, Aytac; Buyukyildiz, Mehmet (Springer Heidelberg, 2024)
Radiation has beneficial applications in medicine and nuclear sciences, but it can also be harmful due to its ionizing properties. So, radiation usage has a significant role in different research fields. In the present study, the Klein-Nishina (K-N) approach was used to evaluate the electronic and energy-transfer cross sections of Water, bone, adipose, soft, long, breast, brain and skin tissues. Compton mass attenuation coefficients (CMAC) and Compton mass energy transfer coefficients (CMACtr) were determined in the energy range 0.284-15 MeV. Different methods, based on the effective charge, were used to determine the parameters of the materials for the energy range. The cross sections were firstly calculated for elements that made up the materials. The investigated parameters of the materials were then determined using the relevant cross sections in the energy range. The results were compared with each other and some possible results from the literature. Klein-Nishina electronic cross sections, Compton mass attenuation coefficients and Compton mass energy transfer coefficients of the studied materials were decreased with increasing gamma-ray energy like the elements. A good agreement was observed for CMACs and CMACtrs based on Z eff1/A and Z eff3/A (Diff. <= 16.4%) for Bone Compact. In addition, a comparison with the literature was done for CaCO3 in CMAC for some photon energies. The maximum difference (%) between used methods and literature was observed as <= 19.0%. The reported data should be useful using the gamma rays in Compton scattering energy region.
Keywords: Scattering; Alloys